Toe1 promotes proliferation and differentiation of neural progenitor cells - Tingting Deng; Xingxing Wu; Yujie Wang; Xiaoqin Fan; Bing Hu (Heliyon)
Toe1 (target of EGR1, member 1) is a 3′- exonuclease in the deadenylase family, essential for the maturation of small nuclear RNAs. Mutations in Toe1 are linked to pontocerebellar hypoplasia 7 (PCH7), a severe neurodegenerative syndrome affecting infants, characterized by progressive neurodegeneration, developmental delay, and genital abnormalities. The pathogenic mechanisms of PCH7 are unclear but are thought to involve abnormal neural stem cell (NSC) development during embryogenesis. This study investigates Toe1's role in NSC development using the C17.2 NSC line. Colony formation, EdU incorporation, and CFSE staining assays showed that Toe1 knockout inhibited C17.2 cell proliferation. Upon inducing differentiation, Toe1 knockout significantly reduced cell dendrites. Immunofluorescence, qPCR, and Western blot analyses indicated that Toe1 knockout suppressed the expression of neuronal marker βIII-tubulin and glial cell marker Gfap, thereby inhibiting C17.2 cell differentiation. Additionally, Toe1 knockout reduced the expression of Dll1 and Jag1, suggesting an inhibition of Notch signaling. High-throughput transcriptome sequencing revealed that Toe1 influenced calcium ion binding, ECM, and amino acid catabolism in undifferentiated C17.2 cells, and peptidase activity, chemotactic factors, ECM, and TNF signaling in differentiated cells. These findings underscore Toe1's critical regulatory role in NSC proliferation and differentiation, with significant implications for developing therapeutic targets for neurodegenerative diseases such as PCH7.